Microstructure characteristics and mechanical properties of Hf0.5Mo0.5NbTiZr refractory high entropy alloy with Cr addition. (February 2021) - Gao, X.J.; Wang, L.; Guo, N.N.; Luo, L.S.; Zhu, G.M.; Shi, C.C.; Su, Y.Q.; Guo, J.J.
Abstract: This paper reported the effect of Cr addition on microstructure, phase constitutes and mechanical properties of the Hf0.5 Mo0.5 NbTiZr refractory high-entropy alloy. The Crx Hf0.5 Mo0.5 NbTiZr (x = 0.1, 0.2, 0.3, 0.4 and 0.5) alloys were composed of one BCC solid solution phase and one CrMoZr-typed Laves phase. This alloy system exhibited the typical dendritic structure after casting. The dendritic structure was refined with the Cr addition. The strength of Crx Hf0.5 Mo0.5 NbTiZr alloys increased and the plasticity also was improved with small amount addition of Cr elements, the strength continued to increase while the plasticity decreased as the concentration of Cr element increased. The homogenization treatment promoted more formation of Laves phase, which significantly increased the strength. Highlights: Crx Hf0.5 Mo0.5 NbTiZr alloy system was composed of one BCC solid solution phase and one CrMoZr-typed Laves phase. The strength of Crx Hf0.5 Mo0.5 NbTiZr alloys increased and the plasticity also increased with small amount of Cr elements. The homogenization treatment promoted more formation of the Laves phase, leading to the increase of the strength.